PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) BERBASIS ETNOMATEMATIKA TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA - Yulia Tiara Tanjung; Muhammad Razali (JURNAL MathEdu (Mathematic Education Journal), 2026)
This research is motivated by the low mathematical critical thinking skills of students. Mathematical critical thinking ability is an important skill in mathematics education. This study aims to determine the effect of the RME approach based on ethnomathematics on mathematical critical thinking ability. The method used in this research is quantitative, with the type of research being Quasi-Experimental, and the research design is a Pretest-Posttest Control Group Design. The population of this study is the students of SMPN 1 Besitang, grade VIII. The sampling was done using the Simple Random Sampling technique. The sample used was class VIII/1 with 32 students as the experimental class and class VIII/2 with 32 students as the control class. The data collection technique used a test instrument given before (pre-test) and after (post-test) the implementation of the research. The data analysis technique used the Mann Whitney U test because the data were not normally distributed. The research results showed: (1) the average pre-test score of mathematical critical thinking skills before applying the PMRI approach based on ethnomathematics for the experimental class was 27.1 while for the control class it was 24.5. (2) The average post-test score of mathematical critical thinking ability after applying the PMRI approach based on ethnomathematics for the experimental class was 62.47, whereas for the control class it was 41.89, (3) the results of data processing using the Mann Whitney U test obtained an Asymp. Sig value of 0.000 < 0.05, so H0 is rejected and H1 is accepted, thus it can be concluded that there is an effect of the RME approach based on ethnomathematics on students' mathematical critical thinking ability. (4) The results of the homogeneity test of both classes show that they do not have different variances or the data is homogeneous.